Correction of congenital ptosis of the eyelid by frontal muscle transposition - Jevtović Dobrica (Vojnosanitetski Pregled)
Congenital ptosis (CP) represents a significant reconstructive problem Numerous studies have not yet provided full and satisfactory results. In this study, we have presented our experience in the surgical treatment of 108 patients by the use of Son Ye Guang's modified method - frontal muscle transposition. A total of 108 patients with CP were surgically treated at the Clinic for Plastic Surgery and Burns of the Military Medical Academy in the period 1991-2000. Unilateral ptosis was operated in 85 patients, and bilateral in 23 patients. CP was more frequently found in males (58.34%) than in females (41.66%). The youngest patient was only 5.5 years old, and the oldest was 42, the average age was 21.3 years. All patients were operated on by the same surgeon, and were monitored monthly during the first six months and then twice a year for the next 3 years. Postoperative results were evaluated after 6 months: the action of raising the eyelids was compared to the full amplitude of movement of the eye on the healthy side. The closure of the eyelids and the symmetry of the palpebral fissure in a steady horizontal view was also assessed. The action of the opening as well as closure of the eyelids in full amplitude was obtained in all operated patients. Asymmetry of the palpebral fissure in a steady horizontal view up to 1 mm did not require additional correction. In 9 cases, asymmetry of the palpebral fissure greater than 1 mm was subsequently corrected. The advantages of this surgical method compared to the other, previously described techniques, were emphasized in the conclusion. The main advantage was the elimination of postoperative lagophthalmos, which represented the problem in all previously used methods.